THE IMPLEMENTATION OF ROAD DAMAGE COMPLAINT SERVICES AT THE DISTRICT LEVEL IN PUBLIC SERVICE DELIVERY - Remalya, Asiel Bernike; Muljanto, Muhammad Agus (Jurnal Governansi, 2025)
The low rate of resolution for road infrastructure complaints submitted through the Si Putra website indicates weak public service implementation. This condition urgently needs improvement as road damage in Tulungagung continues to increase. This study uses policy implementation theory to examine the research object and adopts a qualitative method with data collection techniques including observation, interviews, and documentation. Data analysis in this study follows Creswell’s approach, involving data reduction, presentation, and conclusion drawing, with four informants from PUPR Office staff who are directly involved in managing infrastructure complaints. The findings reveal that the implementation of the road damage complaint service at the PUPR Office of Tulungagung Regency remains suboptimal, as reflected in the low response rate to public reports—only 4% of the 23 complaints submitted via the Si Putra website were addressed. This is due to the absence of internal policy, a shortage of information technology personnel, limited budget, and insufficient public outreach, which leads to a lack of understanding among users about the complaint procedures. As a result, road damage often goes unaddressed, posing risks to road users' safety and diminishing the quality of public services. Therefore, this study emphasizes the need for internal policies that support the complaint system, the addition of human resources, and improved communication and public education to create a more responsive and efficient complaint service.